Implementation of Islamic Religious Education Textbooks Based on Religious Moderation Using the Project-Based Learning (PjBL) Model in Higher Education - Arsyadani Mishbahuddin; Ririn Gusti; Vira Afriyati (GHAITSA : Islamic Education Journal, 2026)
Strengthening religious moderation in higher education has become an urgent need due to the increasing symptoms of intolerance and radicalism among students. Islamic Religious Education (PAI) holds a strategic position in shaping moderate character, but its implementation still faces limitations, particularly in the use of contextual learning models and teaching materials. This study aims to examine the implementation of a religious moderation-based PAI textbook using the Project-Based Learning (PjBL) model, analyze student responses, and identify obstacles that arise during implementation. This study used a qualitative case study design at the University of Bengkulu, involving PAI lecturers and students as research subjects. Data were collected through observation, in-depth interviews, and documentation, then analyzed using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing. Data validity was guaranteed through triangulation techniques. The results of the study indicate that the learning implementation was carried out through the stages of planning, project implementation, and authentic evaluation. The application of this model has been proven to be able to increase active student participation while encouraging the internalization of the values of religious moderation, such as tolerance, inclusivity, anti-violence attitudes, and accommodating local culture. Students also showed a positive response to learning that is more applicable and relevant to their life context, although obstacles were still found in the pedagogical, technical, and cultural aspects. This study contributes to the development of Islamic Religious Education learning models that integrate teaching materials with a project-based approach. The implications of this study emphasize the importance of improving lecturer competence, developing innovative digital-based teaching materials, and the need for further research with a broader scope to test the effectiveness of the model more comprehensively.